(untitled) (Research, Society and Development, 2021)
The increase in the slaughter of females is cyclical in the Brazilian herd, normally influenced by a crisis in the sector, generating a reduction in herds. The slaughter of pregnant females at an advanced stage for a long time was prohibited, for sanitary reasons and for the maintenance of herds. The objective of this study was to characterize and quantify the slaughter of a slaughterhouse in the southern region of the state of Rio Grande do Sul. Data referring to the slaughter of males and females for three consecutive years were evaluated, making up the slaughter of 24,632 cattle. Data were classified by year, month of slaughter, sex and pregnancy (advanced and early). Subsequently, the months of the year were separated by quarters throughout the evaluation period. For the significance of the data the chi-square test was used. Females had the highest rate of slaughter compared to males, especially in February and November. Of the total number of slaughtered females, 12.69% were pregnant, with the highest percentages in the months of March and April. Of the pregnant females, 9.99% were in the final third of pregnancy with the highest accumulated in the months of July to October. The percentage of slaughter of females in advanced pregnancy found in this study is high, which causes losses for the producer, reducing carcass yield. In addition to these facts, the slaughter of pregnant cows is not advisable due to ethical and animal welfare issues.